Peroneal Bypass Versus Endovascular Peroneal Intervention for Critical Limb Ischemia - Mohapatra, Abhisekh (J Vasc Surg, 2018)
OBJECTIVES: The peroneal artery is a well-established target for bypass in patients with critical limb ischemia (CLI). The objective of this study was to evaluate the outcomes of peroneal artery revascularization in terms of wound healing and limb salvage in patients with CLI. METHODS: Patients presenting between 2006 and 2013 with critical limb ischemia (Rutherford IV- VI) and isolated peroneal runoff were included in the study. They were divided into patients who underwent bypass to the peroneal artery and those who underwent endovascular peroneal artery intervention. Demographics, comorbidities, and follow up data were recorded. Wounds were classified by Wound, Ischemia, foot Infection (WIfI) score. The primary outcome was wound healing; secondary outcomes included mortality, major amputation, and patency. RESULTS: Two hundred limbs with peroneal bypass and 138 limbs with endovascular peroneal intervention were included with mean follow-up of 24.0 ± 26.3 and 14.5 ± 19.1 months, respectively (P = .0001). The two groups were comparable in comorbidities with the exception of the endovascular group having more patients with cardiac and renal disease and diabetes mellitus, but fewer patients with smoking history. Based on WIfI criteria, ischemia scores were worse in bypass patients, but wound and foot infection scores were worse in endovascular patients. Peri-operatively, bypass patients had higher rates of myocardial infarction (4.5% vs. 0%, P = .012) and incisional complications (13.0% vs. 4.4%, P = .008). At 12 months, the bypass group compared to the endovascular group had better primary patency (47.9% vs. 23.4%, P = .002) and primary assisted patency (63.6% vs. 42.2%, P = .003) and a trend toward better secondary patency (74.2% vs. 63.5%, P = .11). There were no differences in the rate of wound healing (52.6% vs. 37.7% at one year, P = .09) or freedom from major amputation (81.5% vs. 74.7% at one year, P = .37). In a multivariate analysis, neuropathy was associated with improved wound healing, while WIfI wound score, cancer, chronic renal insufficiency, and smoking were associated with decreased wound healing. Treatment modality was not a significant predictor (P = .15). CONCLUSIONS: Endovascular peroneal artery intervention results in poorer primary and primary assisted patency rates than surgical bypass to the peroneal artery, but provides similar wound healing and limb salvage rates with a lower rate of complications. In appropriately selected patients, endovascular intervention to treat the peroneal artery is a low-risk intervention that may be sufficient to heal ischemic foot wounds.